Hydroelastic damping of low aspect ratio cantilevered plates. (October 2019) - Kohtanen, Eetu A.; Davis, R. Benjamin
Abstract: This study considers the hydroelastic damping of cantilevered flat plates undergoing free vibration in flowing water. Of particular interest are plates with aspect ratios (defined as span length divided by chord length) less than one. Experimental trials involving plates of aspect ratios from 0.3 to 0.7 are conducted in a high-speed water tunnel. The tests involve flow velocities well below those corresponding to hydroelastic instability. Additionally, an unsteady, linear vortex lattice model is coupled to a structural dynamic plate model to predict flow-induced damping as a function of flow speed. The numerical model has been previously used with air, but never with water as the fluid medium. The model is able to predict the hydroelastic damping associated with the first several plate modes with less than 30% error in most cases. While the hydroelastic damping remains linear in the experimental flow regime, at higher flow speeds more complicated hydroelastic damping behavior is predicted. Numerical studies involving mass ratio, aspect ratio, and reduced velocity are conducted to predict hydroelastic damping across a wide parameter space. All else being equal, chordwise bending modes are found to exhibit two to three times greater hydroelastic damping than spanwise bending modes. There is also an inverse relationship between mass ratio and hydroelastic damping. Further, for plates with low aspect ratios and at fixed reduced velocities, hydroelastic damping increases with increasing aspect ratio.